Chapter 7: Prescription Management (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
AuthorDr. Amit Kumar, Associate Professor, Department of Pharmacy Practice, Amity Institute of Pharmacy, Amity University, Lucknow, IndiaAbstractPrescription management encompasses the systematic processes ensuring accurate medication delivery from prescriber to patient while maintaining safety and regulatory compliance. Prescription processing follows a standardized workflow including receipt, verification, interpretation, entry, adjudication, preparation, and final verification, with each step incorporating critical safety checks and legal requirements including DEA regulations for controlled substances. Drug information resources support clinical decision-making through primary literature, tertiary references, electronic databases, and specialized compendia, with selection criteria including currency, authority, objectivity, and accessibility to answer medication questions from patients and healthcare providers. Medication safety practices prevent dispensing errors through system-level approaches including tall-man lettering, barcode verification, physical separation of look-alike products, standardized concentrations, and continuous quality improvement programs analyzing near-misses and actual errors to implement preventive strategies. Dispensing procedures ensure accurate medication preparation through standardized protocols for various dosage forms, with particular attention to specialized requirements for hazardous drugs, compounded preparations, and high-alert medications requiring independent double checks, while maintaining appropriate documentation, patient counseling, and follow-up monitoring. These protocols provide a system for medication provision that balances efficiency with the paramount priorities of accuracy, safety, legal compliance, and patient-centered care.Keywords: Workflow Management; Error Prevention; Information Evaluation; Regulatory Compliance; Patient CounselingVIEW PDF